GURU DALAM KONSEP IMAM AL-GHAZALI - Hamida Olfah (CV. ADIBA AISHA AMIRA, 2023)
Imam al-Ghazali, who is known by the Muslim world as Hujjatul Islam, not only mastered the field of Islamic law, but he is also known as an expert in the field of Sufism, the field of ushul fiqh and even as a philosopher. One of his monumental works is the book Ihya Ulumuddin. The author examines in his work which focuses on an educator or who is often known as a teacher. Indeed, in the view of Imam al-Ghazali, an educator (teacher) must understand the duties, manners of educating, the signs of a good educator so that he tries his best to emulate them and serve as a reference for educating others and also understands the signs bad teacher so that he will try his best to avoid and improve the traits that include the signs of a bad teacher that are still in him. According to Imam al-Ghazali, an educator (teacher) must pay attention to the duties and procedures of politeness in educating, understand and practice the signs of a good educator and stay away from the signs of a bad educator, this is intended to create a perfect Islamic generation. In Indonesia, currently the implementation of education seeks to build a nation that is highly knowledgeable and to develop whole human beings, namely human beings who are faithful and pious as well as knowledgeable. Therefore all educators, teachers and parents as well as the community can actualize Imam al-Ghazali's thoughts in the life of the nation and state.